(untitled) (Journal of Contemporary Philology, 2018)
The Crystal Frontier, аpolyphonic novelby Carlos Fuentes, deals with a number of themes such as migration, class differences, xenophobia, corruption and deconstructs a lot of linguistic, social, cultural, symbolic boundaries, re-examining furthermore the boundaries between genres. In this paper, we further analyze the work from the perspective of the corporeality and the body that represents a starting point from which many borders are delineated: those imposed by fashion, gender, sexual orientation, those derived from the power relations or theapparent freedom of the female body, those who stand between us and our past, between life and death.